Elon Musk - Isaacson, Walter (Simon & Schuster, 2023)
"From the author of Steve Jobs and other bestselling biographies, this is the astonishingly intimate story of the most fascinating and controversial innovator of our era--a rule-breaking visionary who helped to lead the world into the era of electric vehicles, private space exploration, and artificial intelligence. Oh, and took over Twitter"--